2013
DOI: 10.1155/2013/348628
|View full text |Cite
|
Sign up to set email alerts
|

Multifocal Buruli Ulcer Associated with Secondary Infection in HIV Positive Patient

Abstract: Buruli ulcer is a chronic and infectious skin disease, caused by Mycobacterium ulcerans. It leads to large skin ulceration and sometimes bone infection which is responsible for deformities. Here, we report a case of multifocal form of Buruli ulcer associated with secondary infection in a 46-year-old human immunodeficiency virus (HIV) positive woman. The antimycobacterial drugs combined to surgery allowed curing this multifocal case and rose up two relevant issues: the susceptibility of immune reconstitution in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…HIV may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger and ulcerated BU lesions in HIV-infected individuals (Johnson et al 2002;Toll et al 2005;Kibadi et al 2010;Komenan et al 2013;Christinet et al 2014). It also appears that the presence and severity of BU may reflect the level of underlying immune suppression in an HIV-infected person.…”
Section: Challenges In the Co-treatment Of Bu--hivmentioning
confidence: 99%
“…HIV may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger and ulcerated BU lesions in HIV-infected individuals (Johnson et al 2002;Toll et al 2005;Kibadi et al 2010;Komenan et al 2013;Christinet et al 2014). It also appears that the presence and severity of BU may reflect the level of underlying immune suppression in an HIV-infected person.…”
Section: Challenges In the Co-treatment Of Bu--hivmentioning
confidence: 99%
“…A retrospective study conducted in Cameroon revealed that human immunodeficiency virus (HIV) infection may affect the clinical presentation and severity of BU disease with a reported increased incidence of multiple, larger, and ulcerated BU lesions. [16][17][18] Data available on the absorption of antituberculosis medications in tuberculosis (TB)/HIV coinfection compared with HIV-negative patients showed conflicting results. 19,20 Therefore, whether antimycobacterial combination treatment is less efficacious in persons with HIV infection is unknown and needs to be systematically studied.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in TB/HIV co-infection, the incidence of IRIS occurrence is increased in patients who start ART within 30 days of TB treatment initiation [7]. Comparing to the case report recently described in Côte d'Ivoire with multifocal BU lesions developing in a HIV patient with severe immunodepression (baseline CD4 cell counts of 51 cell/ mm3), on month after both BU and HIV treatment initiation [2].…”
Section: Editorialmentioning
confidence: 86%
“…In Côte d'Ivoire, the most sub-Saharan Africa country affected by Buruli ulcer, more than 2000 new cases per year are diagnosed, and HIV and Mycobacterium ulcerans co-infection [2] become more and more frequent.…”
Section: Editorialmentioning
confidence: 99%